The economics of platforms concepts and strategy - Belleflamme, Paul; Peitz, Martin 1967- (Cambridge University Press, 2021)
"According to historians, European trade took off at the end of the 12th century in what is now the North of France, in the county of Champagne.1 It is at this period that this county started to host regular trade fairs, which lasted for six weeks and rotated across six cities. Merchants came from all over Europe because they were confident that they would meet each other at these fairs. This confidence was instilled by the count of Champagne, through his authoritative and clever running of the fairs. Everything was done to provide merchants with a safe and efficient business environment. The count of Champagne actively selected the participants, especially by keeping away dubious businessmen. Once admitted, all participants were on a level playing field, as the count carefully avoided to grant any privilege to anyone. The fair locations were fortified, and impartial institutions were put in place to enforce contracts and resolve disputes. The count also guaranteed loans and the replacement of cash by notary bills to settle transactions. In exchange of all these services, the count took a small share of each transaction and quickly amassed a fortune.
Literaturverzeichnis Seite 242-252
Keywords: Electronic Commerce; Unternehmensmodell; Geschäftsmodell; Systemplattform; Multi-sided platform businesses; BUSINESS & ECONOMICS / Industrial Management